The Education Services of Children for Special Need on Islamic Educational Psychology Perspective - Rahman, Nadya Novia; Rasyid, Miranti; Adhawiyah, Rabiatul (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2022)
This study described the education of children with special needs from the perspective of Islamic education psychology. Education in Indonesia was a right that everyone was obtained. Everyone has the right to receive a proper education, even if that person belongs to the children with special needs category. This research has been a literature study that examined the object of research on the education of children with special needs related to the psychology of Islamic education. This study used documentation techniques in terms of collecting research data. The documentation technique in question was that researchers collect related documents in the form of books, journals, and other scientific works that are relevant to the object of research. An important finding in this study has been that the psychological concept of Islamic education educates the physical and spiritual aspects. Islamic educational psychology has four essential dimensions which must be fulfilled; Physical-Biological Education for Children with Special Needs, Psycho-Educational Education for Children with Special Needs, Spiritual Education for Children with Special Needs, and Socio-Cultural Education for Children with Special Needs. These four dimensions of Education must be balanced to create a balance for the overall growth of children with special needs by training their souls, mind, and body. Studi ini mengambarkan pendidikan anak berkebutuhan khusus dalam perspektif psikologi pendidikan Islam. Pendidikan di Indonesia merupakan suatu hak yang bisa didapatkan oleh semua orang. Setiap orang berhak untuk menerima pendidikan yang layak meskipun orang tersebut termasuk kategori orang yang berkebutuhan khusus. Penelitian ini adalah studi kepustakaan yang mengkaji objek penelitian tentang pendidikan anak berkebutuhan khusus yang dihubungkan psikologi pendidikan Islam. Penelitian ini menggunakan teknik dokumentasi dalam hal pengumpulan data penelitian. Teknik dokumentasi yang dimaksud adalah peneliti mengumpulkan dokumen-dokumen terkait baik yang berbentuk buku, jurnal, maupun karya ilmiah lainnya yang relevan dengan obyek penelitian. Temuan penting dalam penelitian ini adalah konsep psikologi pendidikan Islam tidak hanya mendidik sisi jasmaniah semata tetapi juga dari sisi ruhaniah. Psikologi pendidikan Islam memiliki empat dimensi penting yang harus terpenuhi agar pendidikan anak berkebutuhan khusus bisa berjalan secara maksimal, yaitu Pendidikan Fisik-Biologis Anak Berkebutuhan Khusus, Pendidikan Psiko-Edukatif Anak Berkebutuhan khusus, Pendidikan Ruhaniah-Spiritual Anak Berkebutuhan Khusus dan Pendidikan Sosio-Kultural Anak Berkebutuhan Khusus. Kempat dimensi pendidikan ini harus dilakukan secara seimbang agar menciptakan keseimbangan pertumbuhan kepribadian anak berkebutuhan khusus secara menyeluruh, dengan cara melatih jiwa, akal pikiran, dan fisiknya.